The attitude towards the teaching profession and its relationship to the sense of quality among students of the Faculty of Physical Education and Sports Sciences - عباس, م.د. سحر ياسين; Al-Khaikani, Prof. Dr. Amer Saeed (Sulaimani Journal for Humanities, 2026)
This research aims to determine the following: To know the attitude towards the teaching profession and the sense of quality among students of the College of Physical Education and Sports Sciences at the University of Babylon. To know the relationship between the attitude towards the teaching profession and the sense of quality among students of the College of Physical Education and Sports Sciences at the University of Babylon. To achieve the research objectives, the research community was determined as fourth-year students in the College of Physical Education and Sports Sciences at the University of Babylon, who numbered 176 students. (30) students were chosen randomly, i.e., at a rate of (17.04%). After proving the psychometric properties (validity and reliability) of the two research scales in measuring both the attitude towards the teaching profession and the feeling of quality. They were adopted and applied to the research sample to finally arrive at results that were discussed, and conclusions were reached that were summarized as follows: Students of the College of Physical Education and Sports Sciences at the University of Babylon have a positive and high attitude towards the teaching profession and a relatively high sense of quality. The trend towards the teaching profession among students of the College of Physical Education and Sports Sciences at the University of Babylon is directly related to their degree of sense of quality. The researchers then supplemented their conclusions with several recommendations to solve the research problem.
Keywords: Attitude towards the teaching profession; Sense of quality; Physical education and sports science students